KEANEKARAGAMAN JENIS BURUNG BERDASARKAN GRADIEN TIPE HABITAT DI AREAL TAMBANG EMAS PT NATARANG, KABUPATEN TANGGAMUS, PROVINSI LAMPUNG: Bird Species Diversity Based on Habitat Type Gradients in The Gold Mining Area of PT Natarang, Tanggamus, Lampung Province (Jurnal ForestrIndo, 2025)
Birds are key components of the environment with an important role in maintaining environmental stability. In forested landscapes, the forest environment and the gradient of habitat types influence the richness and diversity of bird species, and bird diversity can be used as a practical measure of environmental stability. An inventory of bird richness and diversity was conducted using a transect approach combined with the Index Point of Abundance (IPA) method to count birds associated with different habitat-type gradients. Six transects, each 200–300 m long, were established in the PT Natarang gold mining area across four habitat types: hilly lowland forest, hilly lowland secondary forest, coffee plantation, and an open area dominated by grasses and shrubs. Along each transect, observation points were set at 50 m intervals. At every point, all birds seen and heard were recorded, noting both the number of individuals and the species, within a 20-minute observation period. A total of 50 bird species were recorded in the PT Natarang concession area. The bird species diversity index ranged from 1.81 to 2.81, with the highest value in the lowland hilly forest habitat gradient and the lowest value in the open habitat gradient. Bird community structure in the concession was dominated by insect-eating birds (48.00%), followed by fruit-eating birds (22.00%). Ten protected species were found in the concession area: Crested Serpent Eagle, Changeable Hawk-Eagle, Black-thighed Falconet, Black Hornbill, Rhinoceros Hornbill, Pied Fantail, Olive-backed Sunbird, Brown-throated Sunbird, Crimson Sunbird, and Little Spiderhunter. These protected species were present along the gradient.